IJTIHAD DALAM HUKUM ISLAM - Ahmad Hanany Naseh (AN NUR: Jurnal Studi Islam, 2012)
This article discusses the importance of ijtihad in order to find the status of Islamic law on an issue when the Qur'an silent and gave no explanation, while in the Sunna was not to be found. But how far things can be incorporated into the treatment of ijtihad. Apart from that discussed also about who is entitled to have the authority as a mujtahid of the requirements are fairly stringent set by previous scholars. So then the question arises that is it still possible of door for ijtihad was open until now? If not, then to whom and where Muslims would find the answers to the legal status of such a complex issue and continues to grow following the developments and progress of the age.